Incident left bundle branch block predicts cardiovascular events and death in hypertensive patients with left ventricular hypertrophy. The LIFE Study - Casper N. Bang; Zhibin Li; Ildri M. Stokke; Sverre E. Kjeldsen; Stevo Julius; Darcy A. Hille; Kristian Wachtell; Richard B. Devereux; Peter M. Okin (Open Exploration Publishing Inc., 2022)
Aim: Whether incident left bundle branch block (LBBB) is associated with increased cardiovascular (CV) morbidity and mortality in treated hypertensive patients with left ventricular hypertrophy (LVH) is unknown. Thus, the present study aimed to examine CV outcomes of incident LBBB in treated hypertensive patients with LVH. Methods: In the Losartan Intervention For Endpoint reduction in hypertension (LIFE) study, 9,193 hypertensive patients with LVH on screening electrocardiogram (ECG) were randomized to losartan or atenolol based treatment. Participants (n = 8,567) did not have LBBB (Minnesota code 7.1) on baseline ECG. Cox regression models controlling for significant covariates assessed independent associations of incident LBBB with CV events and all-cause mortality during 4.8 years mean follow-up. Results: Annual follow-up ECGs identified 295 patients (3.4%) with incident LBBB associated with male gender (P < 0.05), older age, higher Cornell voltage (both P < 0.005) and history of diabetes, isolated systolic hypertension and prevalent CV disease. When adjusted for the history of previous CV disease, diabetes, isolated systolic hypertension, the Framingham risk score, ECG-LVH and randomized study treatment, Cox regression models showed that incident LBBB predicted higher risk of the composite endpoint CV death, myocardial infarction and stroke [hazard ratio (HR) 1.9, 95% confidence intervals (CIs) 1.3-2.9, P < 0.001], CV death (HR 3.0, 95% CIs 1.84-5.0, P < 0.001), heart failure (HR 3.6, 95% CIs 1.9-6.6, P < 0.001) and all-cause mortality (HR 3.0, 95% CIs 2.0-4.3, P < 0.001). Conclusions: These data suggest that among hypertensive patients with ECG-LVH receiving aggressive antihypertensive therapy, incident LBBB independently predicts increased risk of subsequent CV events including congestive heart failure and CV and all-cause mortality (ClinicalTrials.gov identifier: NCT00338260).